Digitalization Initiatives in Rural Areas: an Empirical Analysis From West Java Indonesia - Likuwatan Werang, Nicolaus Petrus; Werang, Maria Lusiana Florentin; Yolandasari, Priscilia; Husnaeni, Yeni; Rizki, Mia (Public Policy and Management Inquiry, 2025)
Digital initiatives have great potential to enhance the quality of life in rural communities. However, for the benefits to be evenly distributed, this process must be inclusive. The West Java government has taken crucial steps through the “Rural Digitalization” program and supporting regulations in 2022. Moreover, barriers such as uneven internet infrastructure, low digital literacy, and minimal use of technology in key sectors such as agriculture, fisheries, and livestock are still major barriers. Coupled with weak coordination between levels of government and budget constraints, it also slows down realisation in the field. This study aims to identify gaps in the initiative of rural digitalisation and offer practical solutions. Through a descriptive qualitative approach and literature study, it was found that access to technology needs to be balanced with locally relevant skills, confidence, and innovation. This study offers a roadmap in the form of mobile-based digital training, a community internet model, and affordable technology solutions. Then, the success of digital initiatives in rural areas depends on long-term collaboration between the government, private sector, and community.